Bid’ah dalam Perspektif Hukum Islam: Klasifikasi dan Konsekuensinya - Lailatul Khamidah; Zahrotul Lailii Mala; Tribuana Tungga Dewi (Yayasan Mutiara Hati Moeslem, 2026)
Bid'ah is an important term in Islamic studies which refers to any form of innovation in religion that does not have a basis in the Al-Qur'an, Sunnah, ijma', or atsar sahaba. This study aims to outline the meaning, classification and consequences of the practice of heresy according to the perspective of classical and contemporary ulama. Based on a literature review, bid'ah is divided into two main categories: bid'ah hasanah (good innovation) and bid'ah dhalalah (misguided innovation), as described by Imam al-Syafi'i and reinforced by scholars such as al-Ghazali. Bid'ah hasanah includes innovations that support the benefit of the people and do not conflict with sharia principles, such as the codification of the Koran and the establishment of Islamic educational institutions. On the other hand, bid'ah dhalalah is an innovation that distorts the basic teachings of Islam, causes deviations from the creed, and weakens the unity of the people. The consequences of implementing bid'ah in religious practice include theological impacts in the form of deviations from the creed, social impacts in the form of divisions in the community, and moral impacts in the form of a decreased commitment to authentic Islamic teachings. Therefore, a proper understanding of the concept and classification of bid'ah is crucial so that innovation in Islam can be directed toward strengthening sharia values, not distorting them.